2017
DOI: 10.7454/jpdi.v3i3.28
|View full text |Cite
|
Sign up to set email alerts
|

Pendekatan Diagnosis dan Tatalaksana Tuberkulosis Intestinal

Abstract: ABSTRAKTuberkulosis (TB) telah menjadi masalah global yang terus membesar seiring dengan bertambahnya jumlah pasien TB. Infeksi TB masih merupakan hal yang umum ditemukan dan merupakan faktor penting terhadap angka kesakitan dan kematian, terutama pada negara yang belum dan sedang berkembang. Kasus Tuberkulosis usus (TB usus) juga meningkat seiring dengan meningkatnya jumlah kasus TB secara umum. Indonesia merupakan Negara ke-2 dengan prevalensi Tuberkulosis TB tertinggi di Asia Tenggara setelah Timor Leste pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
6
0
2
Order By: Relevance
“…Infective colitis includes tuberculous colitis, amoebic colitis, shigellosis, pseudomembranous colitis, and colitis caused by viruses, parasites, or other bacteria. 2,[4][5][6] Colitis causes damage to enterocytes caused by bacteria or toxins that cause inflammation and clinical manifestations of diarrhea, abdominal pain, mucus and bloody diarrhea, and fever. 2,[4][5][6][7][8][9] In this study, we found that there were more female than male patients, which was 65% (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infective colitis includes tuberculous colitis, amoebic colitis, shigellosis, pseudomembranous colitis, and colitis caused by viruses, parasites, or other bacteria. 2,[4][5][6] Colitis causes damage to enterocytes caused by bacteria or toxins that cause inflammation and clinical manifestations of diarrhea, abdominal pain, mucus and bloody diarrhea, and fever. 2,[4][5][6][7][8][9] In this study, we found that there were more female than male patients, which was 65% (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…2,[4][5][6] Colitis causes damage to enterocytes caused by bacteria or toxins that cause inflammation and clinical manifestations of diarrhea, abdominal pain, mucus and bloody diarrhea, and fever. 2,[4][5][6][7][8][9] In this study, we found that there were more female than male patients, which was 65% (Table 2). Studies by Cosnes et al and Betterige et al reported similar results with this study.…”
Section: Discussionmentioning
confidence: 99%
“…Penyakit TB merupakan infeksi multi sistemik yang spesifik, yang dapat menyebabkan manifestasi klinis yang beragam pada tiap sistem organ, sehingga, presentasi klinis penyakit ini juga cukup beragam (Murwaningrum et al, 2017).…”
Section: Pendahuluanunclassified
“…GI TB is defined as MTB infection of the peritoneum, abdominal organs, or abdominal lymphatic system. 5 Clinical manifestation and pathology finding of GI TB are highly variable. It can be nonspecific and mimic other gastrointestinal tract disorders, such as Chron's disease, ulcerative colitis, amoebic enteritis, actinomycosis, enterocolitis, or even malignancy.…”
Section: Case Reportmentioning
confidence: 99%